2015
DOI: 10.1080/1059924x.2015.1106377
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Prevalence of Heat-Related Symptoms and Sun Safety–Related Behavior among Latino Farmworkers in Eastern North Carolina

Abstract: In hot weather, thermal heat generated by the body, combined with environmental heat from the sun, can lead outdoor workers to experience heat-related stress, severe illness, or even death. The aims of this study were to estimate the prevalence of heat-related symptoms and potential risk factors associated with sun safety-related behavior among Latino farmworkers. Data from interviewer-administered questionnaires were collected from a cross-sectional survey among farmworkers (N = 158) from August to September … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 24 publications
1
45
1
1
Order By: Relevance
“…The housing units on the two farms sampled here were not closely inspected by the research team, but no AC units were known to be present. Shade tents or canopies were used in the fields in the IS group, this has been reported by others and also a humanitarian gesture by benevolent employers (Kearney et al, 2016).…”
Section: Discussionmentioning
confidence: 57%
“…The housing units on the two farms sampled here were not closely inspected by the research team, but no AC units were known to be present. Shade tents or canopies were used in the fields in the IS group, this has been reported by others and also a humanitarian gesture by benevolent employers (Kearney et al, 2016).…”
Section: Discussionmentioning
confidence: 57%
“…Mirabelli et al 20 with a longer recall time (any previous year working in U.S. agriculture) found 40 percent of 281 North Carolina farmworkers reported HRI symptoms. Kearney et al 19 estimated an HRI prevalence of 72.3 percent among 158 North Carolina farmworkers, but included more HRI symptoms in the classification. In a Georgia study, Fleischer et al 18 found that one-third of 405 farmworkers experienced at least three HRI symptoms in the previous week.…”
Section: Discussionmentioning
confidence: 99%
“…Research in North Carolina, Florida, Georgia, Oregon, and California has documented high prevalence of HRI and other heat-related conditions among farmworkers. 9,13,[17][18][19][20][21][22] In addition to the health risks of HRI, recent reviews observed increased occupational injury risk in high temperatures among young workers, male workers, and agricultural workers. 23,24 The percent of farmworkers who are women has increased substantially since 2001, [25][26][27] and research is documenting factors related to HRI among women workers.…”
Section: Heat-related Illness and Farmworkersmentioning
confidence: 99%
“…Nationwide, about a quarter of HRI deaths have been reported in the Agriculture, Forestry, Fishing, and Hunting industrial sector which comprises a significant portion of the economy in WA. Prior studies among agricultural workers have described a range of self‐reported prevalence of HRI symptoms, from 35% of workers reporting HRI in the previous 3 months in one study to 72% of workers reporting heat associated symptoms in the previous week 14,15 . The variable prevalence estimates of HRI symptoms can be partially attributed to multiple factors including differences in symptom recognition, HRI reporting, and varying levels of occupational and environmental exposures across sample populations.…”
Section: Introductionmentioning
confidence: 99%